Camrelizumab plus rivoceranib versus sorafenib as first-line therapy for patients with unresectable hepatocellular carcinoma: a cost–utility analysis in China and the United States - Zhao, Qiuling; He, Yimin; Nian, Zilin; Huang, Yongjian; Huang, Ruyi; Lai, Lijun; Yang, Lin (Frontiers in Pharmacology, 2025)
ObjectiveCamrelizumab plus rivoceranib (camr-rivo) has been shown to significantly improve overall survival (OS) in patients with unresectable or advanced hepatocellular carcinoma (HCC) in the CARES-310 trial. However, the cost-utility of this treatment remains unclear. Therefore, this study evaluated the cost–utility of camr-rivo versus sorafenib as a first-line systemic therapy for patients with unresectable or advanced HCC from the perspectives of the Chinese healthcare system and the United States (US) payers.MethodsBased on the CARES-310 trial, a partitioned survival model was constructed to estimate economic costs and health outcomes over a 10-year lifetime horizon. Drug costs were obtained from the public database, Red Book, and relevant literature. Health utility values were derived from the literature. One-way and probabilistic sensitivity analyses were performed. The willingness-to-pay (WTP) threshold was $36,627.25/QALY in China and $150,000.00/QALY in the United States.ResultsCamr-rivo yielded an additional 0.34 quality-adjusted life years (QALY) compared to sorafenib for patients with unresectable or advanced HCC. The incremental costs in China and the United States were $4,762.10 and $92,700.49, respectively, and the incremental cost–utility ratios (ICURs) were $14,174.40/QALY and $272,852.59/QALY, respectively. Sensitivity analyses indicated that the cost of rivoceranib and camrelizumab had the greatest impact on the ICUR in China and the United States. Scenario analyses showed that a price reduction of approximately 30% for camrelizumab and rivoceranib could make camr-rivo a cost-utility option in the United States.ConclusionAt the set WTP threshold, camr-rivo is a cost–utility treatment strategy compared to sorafenib as a first-line therapy for patients with unresectable or advanced HCC in China but not in the United States.